How carbon tax affects the economy and environment: Point of view a corporate taxpayer - As'ad, Ahmad Dzaki; Junaid, Asriani; Nurfadila, Nurfadila; Muslim, Muslim (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the effects of carbon taxation on the economy and the environment from the perspective of corporate taxpayers. The research focuses on coal-fired power facilities in South Sulawesi province, particularly PT PLN Indonesian Power Barru. It explores how carbon taxation influences business operations, government revenue allocation, and environmental sustainability. Research Design and Methodology: A qualitative research approach was employed, utilizing interviews, observations, and document analysis to gather in-depth insights. The case study method was used to analyze the impact of carbon taxation on corporate financial strategies and decision-making processes related to emissions reduction and energy transitions. Findings and Discussion: The findings indicate that while carbon taxation generates revenue that can be allocated to critical sectors such as healthcare and education, it also increases business operational costs. The resulting rise in electricity tariffs poses financial challenges for industries dependent on fossil fuels. In response, businesses explore alternative strategies to reduce emissions, including adopting renewable energy sources and investing in cleaner technologies. Implications: The study highlights the need for a balanced policy approach that ensures economic stability while promoting environmental sustainability. Policymakers should consider implementing incentives to facilitate corporate adaptation to carbon taxes and encourage investment in green energy solutions. Future research should explore the long-term impact of carbon taxation on corporate financial resilience and sustainable economic development in Indonesia.